Adjunctive hyperbaric oxygen therapy in severe burns: Experience in Taiwan Formosa Water Park dust explosion disaster. Issue 4 (June 2017) - Chiang, I-Han; Chen, Shyi-Gen; Huang, Kun-Lun; Chou, Yu-Ching; Dai, Niann-Tzyy; Peng, Chung-Kan
Highlights: Despite major advances in therapeutic strategies for the management of patients with severe burns, there is significant morbidity and mortality. Hyperbaric oxygen therapy (HBOT) is a medical treatment that stimulates the body's natural healing. Our study shows that adjunctive HBOT combined with multidisciplinary burn care can improve sepsis control. Abstract: Background: Despite major advances in therapeutic strategies for the management of patients with severe burns, significant morbidity and mortality is observed. Hyperbaric oxygen therapy (HBOT) increases the supply of oxygen to burn areas. The aim of this study was to determine whether HBOT is effective in the treatment of major thermal burns. Methods: On June 27, 2015 in New Taipei, Taiwan, a mass casualty disaster occurred as fire erupted over a large crowd, injuring 499 people. Fifty-three victims (20 women and 33 men) were admitted to Tri-Service General Hospital. Thirty-eight patients underwent adjunctive HBOT (HBOT group), and 15 patients received routine burn therapy (control group). Serum procalcitonin (PCT) level, a sepsis biomarker, was measured until it reached normal levels (<0.5 μg/L). The records of all patients from June 2015 to March 2016 were analyzed retrospectively. Outcome measures that were compared between the groups included the use of tracheostomy and hemodialysis, total body surface area (TBSA) and the number of skin graft operations, length of hospital stay, infection status, and mortality. Results: The mean age of the patients was 22.4 years, and the mean TBSA was 43%. All the patients survived and were discharged without requiring limb amputation or being permanently disabled. Patient characteristics did not differ significantly between the groups. PCT levels returned to normal significantly faster ( p  = 0.007) in the HBOT group. Conclusion: Multidisciplinary burn care combined with adjunctive HBOT improves sepsis control compared with standard treatment without HBOT. Prospective studies are required to define the role of HBOT in extensive burns.